Severe acute respiratory syndrome coronavirus 2 environmental contamination in hospital rooms is uncommon using viral culture techniques. (12th January 2022) - Warren, Bobby G; Nelson, Alicia; Barrett, Aaron; Addison, Bechtler; Graves, Amanda; Binder, Raquel; Gray, Gregory; Lewis, Sarah; Smith, Becky A; Weber, David J; Sickbert-Bennett, Emily E; Anderson, Deverick J
Abstract: We assessed environmental contamination of inpatient rooms housing coronavirus disease 2019 (COVID-19) patients in a dedicated COVID-19 unit. Contamination with severe acute respiratory syndrome coronavirus 2 was found on 5.5% (19/347) of surfaces via reverse transcriptase polymerase chain reaction and 0.3% (1/347) of surfaces via cell culture. Environmental contamination is uncommon in hospitals rooms; RNA presence is not a specific indicator of infectious virus.